KOMUNIKASI DAN LINGKUNGAN KERJA DALAM MENINGKATKAN SEMANGAT KERJA KARYAWAN PADA ASTON CANGGU BEACH RESORT HOTEL (Studi Pada Aston Canggu Beach Resort Hotel) - I Made Sucita Dana; I Putu Bagus Suthanaya (Universitas Triatma Mulya, 2020)
Employee enthusiasm is a very important thing in supporting the achievement of an organizational goal, if the morale is high then it tends to be able to finish the job well and quickly, on the contrary if the work spirit is low then the work will be less well implemented and employees become dissatisfied. Employee morale can be measured by looking at the percentage of employee absenteeism at work. The problem raised in this study is whether communication (X1) has an effect on increasing employee morale (Y) at Aston Canggu Beach Resort Hotel, does the work environment (X2) have an effect on increasing employee morale (Y) at Aston Canggu Beach Resort Hotel and what communications (X1) and the working environment (X2)influence in increasing employee morale (Y) in Aston Canggu Beach Resort Hotel. The population in this study amounted to 65 people. This study uses the entire population as a sample. Data analysis techniques used are data quality test, classic assumption test, multiple linear regression analysis, t-test analysis and f-test analysis. Results of the analysis showed regression model Y = 2,299 + 0,551X1 + 0,446X2. The conclusion obtained is communication (X1)has a positive effect in improving employee morale (Y) in Aston Canggu Beach Resort Hotel. The work environment (X2) has a positive influence in increasing employee morale (Y) at Aston Canggu Beach Resort Hotel. Communication (X1) and work environment (X2) simultaneously have a positive effect on increasing employee morale (Y) at Aston Canggu Beach Resort Hotel.